2021
DOI: 10.1016/j.jot.2020.12.004
|View full text |Cite
|
Sign up to set email alerts
|

One-stage debridement and bone transport versus first-stage debridement and second-stage bone transport for the management of lower limb post-traumatic osteomyelitis

Abstract: Background Treatment of lower limb post-traumatic osteomyelitis used to be a staged process, with radical debridement of bone and soft tissues at first stage, followed by a second-stage limb reconstruction operation to restore the limb integrity. Some studies recently reported that achieving infection eradication and limb reconstruction at single-stage seems to be an effective method for lower limb infection, but a comparative study remains lacking. This study aims to compare the results of radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…This problem was identified in the 1970s and prompted the use of antibioticloaded PMMA beads by Klemm and Buchholz (Klemm, 1993). There is now encouraging evidence around the use of single-stage surgery, facilitated by modern local antibiotic carriers, with few complications and high infection eradication rates, even in the most complex cases (Masrouha et al, 2018;McNally et al, 2016;Ferguson et al, 2014;Lam et al, 2019;Pincher et al, 2019;Lorentzen et al, 2020;Drampalos et al, 2018;Jiang et al, 2020;Pesch et al, 2020;Hutting et al, 2021;Mifsud et al, 2020;Zhou et al, 2021).…”
mentioning
confidence: 99%
“…This problem was identified in the 1970s and prompted the use of antibioticloaded PMMA beads by Klemm and Buchholz (Klemm, 1993). There is now encouraging evidence around the use of single-stage surgery, facilitated by modern local antibiotic carriers, with few complications and high infection eradication rates, even in the most complex cases (Masrouha et al, 2018;McNally et al, 2016;Ferguson et al, 2014;Lam et al, 2019;Pincher et al, 2019;Lorentzen et al, 2020;Drampalos et al, 2018;Jiang et al, 2020;Pesch et al, 2020;Hutting et al, 2021;Mifsud et al, 2020;Zhou et al, 2021).…”
mentioning
confidence: 99%
“…Surprisingly, the DRD group had lower EFI (49.7 days/cm) and shorter EFT (380.3 days) than the Ilizarov group (56.6 days/cm and 431.7 days). In previous studies, the mean EFI ranged from 0.7 months/cm to 74.8 days/cm 34,36,37,50 . The use of a multiple-osteotomy (multifocal) technique could shorten the distraction period, and a low EFI is often associated with improvement in postoperative functional recovery 36,50 .…”
Section: Discussionmentioning
confidence: 85%
“…However, this technique has several drawbacks: long operative time, a high rate of unplanned operations, and recurrent infections. Therefore, many modified bone-transport techniques with satisfactory outcomes have been described [34][35][36][37][38][39][40][41] .…”
mentioning
confidence: 99%
“…McNally et al reported on the application of an absorbable, gentamicin-loaded, calcium sulphate/hydroxyapatite ceramic and found a recurrence rate of only 6% in 100 patients treated with a single-stage operation for chronic osteomyelitis (including 71 FRIs) [ 19 ]. Zhou et al found a recurrence rate of 6% in 100 patients treated for posttraumatic osteomyelitis with an antibiotic-loaded calcium sulfate vehicle [ 41 ]. Furthermore, a review by Pesch et al evaluated the treatment of FRI/osteomyelitis cases with a ceramic bone substitute in eight studies, including their own patient cohort and found a mean recurrence rate of 8.3% (range: 0–14.3%) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%